2003
DOI: 10.1038/nrm1103
|View full text |Cite
|
Sign up to set email alerts
|

Sphingosine-1-phosphate: an enigmatic signalling lipid

Abstract: The evolutionarily conserved actions of the sphingolipid metabolite, sphingosine-1-phosphate (S1P), in yeast, plants and mammals have shown that it has important functions. In higher eukaryotes, S1P is the ligand for a family of five G-protein-coupled receptors. These S1P receptors are differentially expressed, coupled to various G proteins, and regulate angiogenesis, vascular maturation, cardiac development and immunity, and are important for directed cell movement.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

33
1,972
1
7

Year Published

2006
2006
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 1,928 publications
(2,013 citation statements)
references
References 89 publications
33
1,972
1
7
Order By: Relevance
“…This role is facilitated by the monoamine oxidases [65]. It has long been known that ceramide accumulation leads to cell death/apoptosis, what is somewhat paradoxical though, is the fact that one of its downstream metabolites sphingosine-1-phosphate (S1P) is a growth promoter and support cell survival [66]. Indeed, S1P preincubation has been shown to prevent mortality induced by hypoxia [67,68].…”
Section: Ceramide and Reactive Oxygen Speciesmentioning
confidence: 99%
“…This role is facilitated by the monoamine oxidases [65]. It has long been known that ceramide accumulation leads to cell death/apoptosis, what is somewhat paradoxical though, is the fact that one of its downstream metabolites sphingosine-1-phosphate (S1P) is a growth promoter and support cell survival [66]. Indeed, S1P preincubation has been shown to prevent mortality induced by hypoxia [67,68].…”
Section: Ceramide and Reactive Oxygen Speciesmentioning
confidence: 99%
“…The function of S1P is go through its receptors S1PRs (S1PR1‐5) which belongs to the G‐protein coupled receptor (GPCR) family 2 and each receptor, respectively, involved in cell growth, apoptosis, proliferation, angiogenesis, chemo resistance, or vascular stability 5, 13, 14, 15. It is also a chemotactic factor for immune cell trafficking 5, 16, 17 and a microenvironmental regulator for cancer development 18. The growth rate of breast cancer cells was found to be decreased in SPHK1 or SPHK2 deficient mice 19.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, it has been demonstrated that substantial crosstalk exists between S1P and other proangiogenic growth factors such as VEGF, EGF, PDGF, bFGF and IL-8. For example, S1P transactivates EGF (Shida et al, 2004) and VEGF2 receptors (Spiegel and Milstien, 2003) and VEGF upregulates S1P 1 receptor expression (Igarashi et al, 2003). Also, S1P, acting via S1P 1 and the 'VEFG axis,' is required for hind-limb angiogenesis and neovascularisation (Chae et al, 2004).…”
Section: Sphingosine-1-phosphate and Tumour Angiogenesismentioning
confidence: 99%